Predicting Outcome in Adult Patients With Congenital Heart Disease: A Systematic Review and Meta-Analysis on the Predictive Value of NT-proBNP and High-Sensitive Troponin T - Sara Rashki Ghalenoo; Zohreh Mahmoodi (International Journal of Vascular Medicine, 2025)
Conclusion: In conclusion, this meta-analysis shows the prognostic value of both NT-proBNP and hs-TnT in adults with congenital heart disease. Each of these markers offered a distinct but complementary clinical insight. Although methodological differences of the included studies limit direct comparison, our systematic review supports the potential value of incorporating both biomarkers into routine risk assessment.